Qur'ānic Methodology for Religious Vocation - Khan, Musaddiq Majid (Academy of Language Studies & Academy of Contemporary Islamic Studies, UITM, Ipoh, 2016)
Al-Din is the natural reality Allah SWT embedded in the human nature, as it was necessary for comprehensive welfare of man as an individual and society. Muslim scholars without any exception, hence, the entire Muslim Ummah is unanimous in the fact that any human act based on anything other than the Qur‟ānic concept of al-Din carries no weight in the eyes of Allah. (Al-,Imrān:85) The Qur‟ān calls man to al-DÊn in many ways, particularly through attracting attention towards the natural and human phenomena which serve as the sources for understanding the message that the power of Allah is unfathomable. In this study, the researcher will present some important methods used in the Qur'ān to call the human beings towards al- Din.